2021
DOI: 10.1053/j.gastro.2021.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Interleukin-6 Trans-signaling Inhibition by Olamkicept (sgp130Fc) in Patients With Active Inflammatory Bowel Disease

Abstract: BACKGROUND & AIMS: A large unmet therapeutic need exists in inflammatory bowel disease (IBD). Inhibition of interleukin (IL)-6 appears to be effective, but the therapeutic benefit of a complete IL6/IL6 receptor (IL6R) blockade is limited by profound immunosuppression. Evidence has emerged that chronic proinflammatory activity of IL6 is mainly mediated by transsignaling via a complex of IL6 bound to soluble IL6R engaging the gp130 co-receptor without the need for membrane-bound IL6R. We have developed a decoy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
123
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(126 citation statements)
references
References 44 publications
3
123
0
Order By: Relevance
“…Further, while the focus to date has been blockade of both classic and trans-signaling with tocilizumab and sarilumab in COVID-19, selective blockade of trans-signaling is an area for further investigation (Figure 1). Olamkicept, a novel inhibitor of IL-6/sIL-6R and therefore selective inhibitor of trans-signaling, has shown promising activity in a phase II trial of inflammatory bowel disease, 14 as well as a murine sepsis model. 15 Thinking ahead to future pandemic viruses, improving our ability to identify and treat maladaptive viral immune responses through improved understanding of IL-6 signaling and blockade is imperative.…”
Section: Commentarymentioning
confidence: 99%
“…Further, while the focus to date has been blockade of both classic and trans-signaling with tocilizumab and sarilumab in COVID-19, selective blockade of trans-signaling is an area for further investigation (Figure 1). Olamkicept, a novel inhibitor of IL-6/sIL-6R and therefore selective inhibitor of trans-signaling, has shown promising activity in a phase II trial of inflammatory bowel disease, 14 as well as a murine sepsis model. 15 Thinking ahead to future pandemic viruses, improving our ability to identify and treat maladaptive viral immune responses through improved understanding of IL-6 signaling and blockade is imperative.…”
Section: Commentarymentioning
confidence: 99%
“…Interestingly, we have shown that specific blockade of IL-6 trans-signaling was as effective as the blockade of global IL-6 activity by a neutralizing antibody indicating that IL-6 trans-signaling represents the pro-inflammatory IL-6 activity ( Scheller et al, 2011 ) whereas IL-6 signaling via the membrane bound IL-6R was rather protective e.g., in the case of bacterial infections ( Sodenkamp et al, 2012 ; Hoge et al, 2013 ). Having shown that the sgp130Fc protein protected mice in models of inflammatory bowel disease ( Atreya et al, 2000 ; Mitsuyama et al, 2006 ) we could recently demonstrate the efficacy of the sgp130Fc proteins in patients with Crohn’s disease and ulcerative colitis ( Schreiber et al, 2021 ).…”
Section: The Interleukin-6 Family Of Cytokinesmentioning
confidence: 99%
“…T he diagnosis of Wilson disease (WD) can be determined by a combination of parameters aiming to detect copper accumulation. In this article from Collins et al, 1 a new approach to the diagnosis of WD is proposed. In current clinical practice, low ceruloplasmin levels are used as a minimal screening test, followed by Kayser-Fleischer ring assessment, 24-hour urine collection, liver biopsy for copper quantification, and brain magnetic resonance imaging for demonstration of copper-related changes in the basal ganglia.…”
Section: Expanding the Diagnostic Toolkit Of Wilson Disease With Atp7b Peptidesmentioning
confidence: 99%
“…In this issue of Gastroenterology, Collins et al 1 adopt a new approach to the diagnosis of WD based on the quantification of ATP7B protein concentration derived from measurement of 2 surrogate peptides in patient dried blood…”
Section: Expanding the Diagnostic Toolkit Of Wilson Disease With Atp7b Peptidesmentioning
confidence: 99%
See 1 more Smart Citation